Leflunomide and teriflunomide: altering the metabolism of pyrimidines for the treatment of autoimmune diseases. Issue 3 (May 2015) - Fragoso, Yara Dadalti; Brooks, Joseph Bruno Bidin
<x xml:space="preserve">Abstract</x> Leflunomide modulates T-cell responses and induces a shift from the Th1 to Th2 subpopulation. This process results in a beneficial effect in diseases in which there is good evidence that T cells play a major role in both initiation and perpetuation of the inflammatory condition. Leflunomide has been successfully used for treating rheumatoid arthritis and psoriatic arthritis for many years. The active metabolite of leflunomide is teriflunomide, which has been approved for treating multiple sclerosis. Teriflunomide, just like the mother drug, inhibits dihydro-orotate dehydrogenase and synthesis of pyrimidine. The present review presents and discusses the safety profiles of leflunomide and teriflunomide, two drugs that are indeed the same, considering that much can be learned from the reported side effects of both.